2015
DOI: 10.1007/s10103-015-1797-3
|View full text |Cite
|
Sign up to set email alerts
|

Lasers in esthetic treatment of gingival melanin hyperpigmentation: a review article

Abstract: The health and suitability of mouth components play an important role towards defining facial attractiveness. An important component of the oral cavity is the color of the gingival tissue. Gingival melanin hyperpigmentation is caused by several reasons and affects people across ethnicity, race, age, and both gender. Lasers are presently being used for gingival melanin depigmentation. In this article, we reviewed studies on laser parameters, duration of gingival healing, pain perception during and after the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
3
19
0
8
Order By: Relevance
“…is is justified as the diodes have deeper penetration and thermal impact on the tissue which leads to more coagulation efficacy [31]. ese results agree with many papers that used the lasers and notified that the high control in bleeding is achieved when using them [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]32]. Statistically, there was no difference between the comparative groups (P < 0.102).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…is is justified as the diodes have deeper penetration and thermal impact on the tissue which leads to more coagulation efficacy [31]. ese results agree with many papers that used the lasers and notified that the high control in bleeding is achieved when using them [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]32]. Statistically, there was no difference between the comparative groups (P < 0.102).…”
Section: Discussionsupporting
confidence: 68%
“…Positive opinions and conclusion have been discussed. Some papers suggest that the laser is an effective tool in gingival depigmentation specially when used by an experienced operator [8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]29]. is study meant to check 3 different laser wavelengths and to clarify the different outcomes among them, especially as diode laser users have increased in the past few years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, gingiva affect the beauty of smile. 1,2) The most common cause of gingival pigmentation is physiologic due to the over production of melanin gran-ules from melanocytes. 3,4) The oldest documented text about unpleasant dark gingival color is related to the study of Ginwalla et al (1966), they suggested the removal of these pigmented area 5) .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, gingival depigmentation with lasers are been mentioned as the most effective, compatible, valid methods and choice of treatment among clinicians 1,17) .…”
Section: Introductionmentioning
confidence: 99%